Development of thin-film micro-outlets for spatially constraining local PO2 perturbations to capillaries in vivo - Kiley, Meghan E.; Sové, Richard J.; Smith, Reilly H.; Wells, Brenda N.; Russell McEvoy, Gaylene M.; Fraser, Graham M. (Frontiers in Physiology, 2025)
ObjectiveTo develop and validate thin-film micro-outlet devices to study microvascular blood flow responses to localized changes in skeletal muscle oxygen concentration ([O2]).Methods30 male Sprague-Dawley rats (159–194 g) were anesthetized and instrumented to maintain cardiovascular state. The extensor digitorum longus (EDL) muscle was dissected, isolated, and reflected over a gas exchange chamber (GEC) mounted in the stage of an inverted microscope. The GEC and EDL were coupled via a composite, gas permeable membrane, and a gas impermeable film fabricated with laser machined micro-outlets of specific diameters (200, 400, 600, and 1,000 μm). [O2] in the EDL was dynamically manipulated with step-wise oscillations between 7% (1 min) → 12% (1 min) → 2% (1 min) → 7% (1 min), and step challenges from 7% (1 min) → 2% or 12% (2 min), while recording intravital video for capillary RBC oxygen saturation (SO2) and hemodynamic measurements. Oxygen diffusion between tissue and micro-outlet devices was modelled using a finite element mass transport model to further validate experimental results.Results[O2] oscillations imposed on capillaries directly overlying 400 μm micro-outlets caused significant changes in RBC SO2 at 12% and 2% [O2], compared to 7% [O2] (p < 0.0001). [O2] oscillations caused significant changes in capillary RBC supply rate (SR) at 2% [O2] versus 7%, and were significantly different at 2% compared to 12% [O2] (p < 0.0014). Similarly, [O2] challenges imposed on capillaries overlying 200 μm micro-outlets also caused significant changes in RBC SO2 at 2% [O2], compared to 7% [O2] (p < 0.0001), and caused significant changes in SR at 2% [O2] compared to 7% (p < 0.0001).ConclusionOur composite thin-film devices were fabricated and validated to spatially confine oxygen perturbations to capillaries using micro-outlets of varying diameters. These results demonstrate that our devices can manipulate capillary SO2 and alter capillary RBC SR in vessels directly overlying the micro-outlet without affecting capillary SO2 at a distance from the outlets. Our novel composite thin-film micro-outlet devices demonstrate that capillary blood flow responses can be provoked by manipulating [O2] in tissue regions as small as ∼200 μm in diameter.